Cryptocurrency : Invisible or Invincible Currency – Answers for Unanswered Questions - Narayanaswamy, T.; Karthika, P. (Indian Journal of Finance, 2018)
The study is a bird’s eye view on various elements of virtual cryptocurrency that has been in existence from 2009 onwards. The information required for the study was collected from the media reports. In the first section of the paper, origin and features of bitcoin were discussed. In the next section, general risks and transactional risks with suitable examples and a few caselets were explained. Majority of the news content described that cryptocurrency does not carry the features of investment, and it is merely a form of speculation. The media reports indicated many fraudulent cryptocurrency transactions running into several lakhs because of hidden identity of people that opens the door for hacking money without much efforts. Unless the technology used to create cryptocurrency is transparent and regulated, it will not safeguard the money of investors gettingÂ trapped into it. The last part of the study indicated the international acceptance of cryptocurrency (both in developed and developing countries). It was found that majority of the countries did not encourage the use of bitcoins. Hence, this study would be of great use to the people who want to invest in cryptocurrencies.